UJI FITOKIMIA DAN ANTIBAKTERI FRAKSI AIR KULIT BATANG TANAMAN TURI (Sesbania grandiflora L.) TERHADAP BAKTERI Staphylococcus aureus - Ni Luh Made Rahayu Widya Lestari; Desak Putu Risky Vidika Apriyanthi; Ni Putu Rahayu Artini (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2024)
Staphylococcus aureus is a bacteria that can cause skin and soft tissue infections such as urinary tract infections, pneumonia, mastitis, and meningitis. Staphylococcus aureus infections are usually treated with antibiotics, but most antibiotics are resistant to the bacteria and have side effects of toxicity to the body. One alternative to finding new antibacterials from natural ingredients is to use turi plants. This study aims to determine the content of secondary metabolites in the water fraction of the bark of turi (Sesbania grandiflora L.) and to determine the antibacterial activity of the water fraction of the bark of turi (Sesbania grandiflora L.) against Staphylococcus aureus. This research is an experimental study, using the bark fraction of the turi plant. The fraction was obtained after the fractionation process from the bark extract of turi (Sesbania grandiflora L.) so that the water fraction was divided into several concentrations, namely 25%, 50%, 75%, and 100%. Antibacterial activity test was carried out by well diffusion method. The results of this study indicate that the water fraction of the bark of turi (Sesbania grandiflora L.) contains secondary metabolites of alkaloids, tannins, saponins, steroids, and phenolics. The antibacterial activity produced was included in the moderate category at a concentration of 25% with an inhibition zone of 9.70 ± 0.14 mm, a strong category at concentration of 50% and 75% with an inhibition zone of 12.37 ± 0.25 mm, and 18.47 ± 0.23 mm, in addition to the category of very strong at a concentration of 100% with an inhibition zone of 23.47 ± 0.09 mm.